2005
DOI: 10.1292/jvms.67.1019
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity and Chronic Toxicity in Mice and Rats Exposed by Inhalation to para-Dichlorobenzene for Two Years

Abstract: ABSTRACT. Carcinogenicity and chronic toxicity of para-dichlorobenzene (p-DCB) were examined by exposing 50 BDF 1 mice and 50 F344 rats of both sexes by inhalation to p-DCB vapor at a target concentration of 0 (control), 20, 75 or 300 ppm for 6 hr/day, 5 days/ week and 2 years. Incidences of hepatocellular carcinomas, hepatoblastomas and hepatic histiocytic sarcomas in the 300 ppm-exposed male mice, and hepatocellular adenomas and carcinomas and hepatoblastomas in the 300 ppm-exposed female mice were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Studies in laboratory animals indicate that the main human health concerns associated with p-dichlorobenzene are adverse and carcinogenic effects in the liver (Aiso et al, 2005a(Aiso et al, , 2005bHollingsworth et al, 1956;Naylor & Stout, 1996;NTP, 1987), although it is not conclusively established that this site is the only or the most sensitive target of exposure. The data reported below show that while certain endpoints such as carcinogenicity are fairly well studied (Aiso et al, 2005a(Aiso et al, , 2005bNTP, 1987a), other chronic effects due to the inhalation or ingestion of this compound have not been sufficiently studied. These data gaps are a cause of concern given the wide availability and use of p-dichlorobenzene-containing household products.…”
Section: Hazard Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in laboratory animals indicate that the main human health concerns associated with p-dichlorobenzene are adverse and carcinogenic effects in the liver (Aiso et al, 2005a(Aiso et al, , 2005bHollingsworth et al, 1956;Naylor & Stout, 1996;NTP, 1987), although it is not conclusively established that this site is the only or the most sensitive target of exposure. The data reported below show that while certain endpoints such as carcinogenicity are fairly well studied (Aiso et al, 2005a(Aiso et al, , 2005bNTP, 1987a), other chronic effects due to the inhalation or ingestion of this compound have not been sufficiently studied. These data gaps are a cause of concern given the wide availability and use of p-dichlorobenzene-containing household products.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…In a chronic inhalation study, groups of 50 male and female F344 rats and 50 male and female BDF 1 mice were exposed to p-dichlorobenzene at concentrations of 0, 20, 75, or 300 ppm for 6 h/d, 5 d/week for 104 wk (Aiso et al, 2005a). The only exposure-related finding in either species or gender following histological examinations of reproductive system tissues was mineralization of the testis in male mice with incidences of this lesion significantly increased at ≥75 ppm (incidences in the control to high dose groups were 27/49, 35/49, 42/50, and 41/49).…”
Section: P-dichlorobenzenementioning
confidence: 99%
“…pDCB is a liver carcinogen in male and female B6C3Fl mice and a kidney carcinogen in male rats [16][17][18]. Increased cell proliferation has also been observed in the livers of both male and female mice and in male rat kidney, corroborating the reported carcinogenic effects of pDCB in these tissues [19].…”
Section: Introductionmentioning
confidence: 53%
“…Although the best described adverse health effect of pDCB are carcinogenic in nature, other studies have reported that pDCB produces overt hematotoxicity, nephrotoxicity, hepatotoxicity, neurotoxicity, and damage to the lungs, both in experimental animals and humans [17,18,[52][53][54][55]. pDCB exposure has also been reported to induce addiction and resultant withdrawal encephalopathy [52].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorinated benzenes are also widespread groundwater contaminants due to their extensive use in the synthesis of plastics, dyes, and pharmaceutical products as well as their use as solvents, pesticides, and degreasers. Both of these classes of groundwater contaminants pose a threat to human and environmental health given that they are carcinogenic (Dean, 1985;Aiso et al, 2005) and can be persistent in groundwater (Acton and Barker, 1992). Determining remediation strategies and long-term treatment plans for contaminated aquifers requires an understanding of the fate and distribution of the contaminants in the subsurface (Wiedemeier et al, 1995).…”
Section: Introductionmentioning
confidence: 99%